2008
DOI: 10.1584/jpestics.g07-09
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal properties of bistrifluron against sycamore lace bug, Corythucha ciliata (Hemiptera: Tingidae)

Abstract: Bistrifluron, a member of the benzoylphenylurea (BPU) class, was developed in the Republic of Korea as an inhibitor of chitin synthesis. This study examined the effect of bistrifluron on insecticidal activity, adult longevity, fecundity and ovarian development in the sycamore lace bug, Corythucha ciliata. The results showed that bistrifluron had no direct effect on the egg, but produced 100% mortality in larvae hatched within 24 hr with a similar effect regardless of the instars of the larvae (LC 50 ϭ0.01-0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Various methods to control SLB have been investigated. Yoon et al [20]) examined the effect of bistrifluron (chitin synthesis inhibitor), and Pavela et al [64] applied azadirachtin (active ingredient of the neem tree Azadirachta indica A. Juss.)…”
Section: Introductionmentioning
confidence: 99%
“…Various methods to control SLB have been investigated. Yoon et al [20]) examined the effect of bistrifluron (chitin synthesis inhibitor), and Pavela et al [64] applied azadirachtin (active ingredient of the neem tree Azadirachta indica A. Juss.)…”
Section: Introductionmentioning
confidence: 99%
“…However, the modification for the two amide moieties was relatively seldom reported, especially the alteration of the amide bridge, a key pharmacophore that links the benzene ring and the N -pyridylpyrazole heterocycle, was not much reported in previous patents. It is known that acylurea or acylthiourea compounds, representing an important class of biologically active molecules, such as benzoylphenylureas (e.g., diflubenzuron), are a familiar type of insect growth regulators (IGRs), which have attracted considerable attention for decades because of their unique mode of action and low toxicity to nontarget organisms (beneficial arthropods). We also found some N -pyridylpyrazole acylthioureas showed favorable insecticidal activities in our preliminary research, which encouraged us to further synthesize novel compounds with bridge-modified structure . Heterocycles such as oxadiazole, thiazoline, and other heterocycles are important pharmacophores for insecticidal molecular design.…”
Section: Introductionmentioning
confidence: 62%
“…It is safe and harmless for the environment (IOBC Class 1). 15 In some studies, its highly efficient controlling results for insects have been confirmed, such as Plutella xylostella, 16 Corythucha ciliata, 17,18 Coptotermes lacteus 19 and so on. Although bistrifluron has not been registered in China, it is reported that S. litura have developed moderate resistance levels in the field and laboratory strains through continuous screening with some concentrations of bistrifluron.…”
Section: Introductionmentioning
confidence: 90%